1961
DOI: 10.1084/jem.113.5.899
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Glomerulonephritis

Abstract: Daily injections of any one of several foreign serum proteins produced in rabbits functional and morphological alterations similar to those seen in acute, subacute, and chronic human glomerulonephritis. The critical factor determining whether a rabbit would develop renal disease and the type of disease developed was the amount of antibody the rabbit formed. Those responding with much antibody were likely to develop an acute, self-limited glomerulonephritis and to be subsequently immune to further renal damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
1
2

Year Published

1962
1962
1972
1972

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 613 publications
(109 citation statements)
references
References 18 publications
4
102
1
2
Order By: Relevance
“…It is unlikely that the technique described in this paper is related to an antigen-antibody complex mechanism such as Dixon has employed in producing glomerulonephritis in rabbits (17). The bulk of evidence in the autoallergic disease suggests each disease is mediated by cells (sensitized or antibody-bearing), but the evidence in the sheep nephritis is incomplete for either vector.…”
Section: Glomierulonephritis Induced In Sheepmentioning
confidence: 93%
See 1 more Smart Citation
“…It is unlikely that the technique described in this paper is related to an antigen-antibody complex mechanism such as Dixon has employed in producing glomerulonephritis in rabbits (17). The bulk of evidence in the autoallergic disease suggests each disease is mediated by cells (sensitized or antibody-bearing), but the evidence in the sheep nephritis is incomplete for either vector.…”
Section: Glomierulonephritis Induced In Sheepmentioning
confidence: 93%
“…Most attempts to produce experimental animal nephritis by immunological models have centered chiefly on the production of nephritis by single or repeated intravenous injections of foreign protein (15)(16)(17), antigen-antibody complexes (18), or anti-kidney antibodies (13). Heteronephrotoxic sera have been considered to be highly species specific (19,20), but Steblay and Lepper (21) have shown that rabbit antihuman glomerular basement membrane serum will produce nephritis in dogs.…”
mentioning
confidence: 99%
“…In contrast, complex induced nephritis and nephrotoxic serum nephritis show preferential deposition of gamma globulin and complement in the capillary walls (17,30). AD also appears to differ from these other types of glomerular injury in that it features a marked proliferation of rnesangial ceils with only minor damage to the remainder of the capillary wall, while experimental complex-induced, nephrotoxic serum-induced, or naturally occurring human glomerulonephritis primarily affects the peripheral glomerular capillary wall with variable damage to the mesangial areas.…”
Section: Serum Proteinmentioning
confidence: 97%
“…In experimental animals it is known that amounts of antigen-antibody complexes too small to be detectable in the analytical ultracentrifuge are associated with the lesions of serum sickness and at least one type of experimental glomerulonephritis (28)(29)(30). In the AD-affected mink no direct evidence was found that the circulating protein-protein complexes were biologically harmful.…”
Section: Serum Proteinmentioning
confidence: 99%
“…Abundant data derived from experimental models have shown that the presence of complexes in the circulation coincides temporally with the development of the lesions, e.g., acute glomerulonephritis and vasculitis (5,6) and chronic glomerulonephritis (7). In these studies the complexes were demonstrable in the lesions, and it was reasonably presumed that they reached their destination in the tissues after passage through the circulation.…”
Section: Platzs 21 and 22mentioning
confidence: 98%